5-Carboxyfluorescein: intrinsic peroxidase-like catalytic activity and its application in the biomimetic synthesis of polyaniline nanoplatelets. Issue 30 (20th July 2017) - Hu, Qiong; Li, Li; Sun, Gengzhi; Li, Dali; Kong, Jinming; Huang, Wei; Zhang, Xueji
Abstract : 5-Carboxyfluorescein possesses intrinsic peroxidase-like catalytic activity and can be used for the biomimetic synthesis of polyaniline nanoplatelets under harsh conditions. Abstract : 5-Carboxyfluorescein is verified to possess intrinsic peroxidase-like catalytic activity and can serve as a robust artificial peroxidase for the biomimetic synthesis of polyaniline nanoplatelets under harsh conditions. Our work discloses the potential of using this small molecule as a peroxidase surrogate for the biomimetic synthesis of nanostructured polymers.